2015
DOI: 10.1155/2015/375174
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low‐Frequency Sound Stimulation on Patients with Fibromyalgia: A Clinical Study

Abstract: Researchers have hypothesized that thalamocortical dysfunction plays a role in fibromyalgia. The use of low-frequency sound stimulation to ameliorate thalamocortical dysfunction has also been investigated, and has shown promise in treating certain pain conditions. Accordingly, the authors of this study aimed to assess the effects of treatment with low-frequency sound stimulation among patients with fibromyalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 76 publications
4
44
0
4
Order By: Relevance
“…However, little is known regarding the application of vibroacoustic stimulation in the treatment of chronic pain conditions. Previous clinical studies have explored the use of rhythmic sensory stimulation to treat fibromyalgia [3638]. Rhythmic sensory stimulation (RSS) broadly refers to the use of sensory events - including vibrotactile, auditory, and visual flickering stimuli - applied in pulsed forms with repeated short, transient stimulus events at regular intervals, or in continuous forms which generate oscillating (e.g., sinusoidal) stimulus patterns [39].…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known regarding the application of vibroacoustic stimulation in the treatment of chronic pain conditions. Previous clinical studies have explored the use of rhythmic sensory stimulation to treat fibromyalgia [3638]. Rhythmic sensory stimulation (RSS) broadly refers to the use of sensory events - including vibrotactile, auditory, and visual flickering stimuli - applied in pulsed forms with repeated short, transient stimulus events at regular intervals, or in continuous forms which generate oscillating (e.g., sinusoidal) stimulus patterns [39].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the VA method have shown a significant improvement in many somatic and functional disorders, e.g. reduction in pain, including fibromyalgia [6][7][8], decrease in muscle tension and spasms [9][10][11], and a reduction in the parameters of blood pressure, pulse rate and muscle oscillation [12]. Experiments with the method have produced an improvement in motor function in the treatment of patients with Parkinson's disease [13].…”
Section: Vibroacoustic Treatment Methodsmentioning
confidence: 99%
“…Because thalamocortical dysrhythmia is implicated in FM and that low-frequency sound stimulation can play a regulatory function by driving neural rhythmic oscillatory activity, volunteers with FM were subjected to 23 min of low-frequency sound stimulation at 40 Hz, delivered using transducers in a supine position. Although no adverse effects in patients receiving the treatment, no statistically and clinically relevant improvement were observed [ 117 ]. On the other hand, gamma-frequency rhythmic vibroacoustic stimulation was found to decrease FM symptoms (depression, sleep quality and pain interference) and ease associated comorbidities (depression and sleep disturbances), opening new avenues for further investigation of the effects of rhythmic sensory stimulation on chronic pain conditions [ 118 ].…”
Section: Therapymentioning
confidence: 99%